ON SOME MODELS OF LINEAR OPTIMIZATION WITH APPLICATIONS - CĂTĂLIN-ILIE MITRAN (Annals of the University of Petrosani: Economics)
The purpose of this paper is to present an economic model of profit maximization in case of a factory that has a number of equipments that must produce a certain number of workpieces in terms of time and profit specified. Using two mathematical models for solving linear optimization problems will be solved a particular case of the mentioned economic problem. One of the method is based on graphics resolution and the other on the simplex algorithm. First of all will be presented the data of the problem with a particular case for solving and after these a short presentation of the two above mentioned methods followed by the itself solve of the problem using these methods and the results analysis.